Modelling of Failures Effect of Open Transmission System for Safety Critical Applications with the Intention of Safety - Franekova, M.; Luley, P.; Ondrasina, T. (Elektronika ir Elektrotechnika, 2014)
The paper deals with the problem of modelling safety features of open transmission system used within safety-related applications. The basic principles of modelling failures effect to safety of open transmission system and standards used in the process of safety evaluation are summarised in the paper. The practical part is oriented to description of realized Markov’s model for determination of random failures effects to safety of safety-related wireless communication system with safety a cryptography codes. The model reflects the safety analysis of failures effect caused by electromagnetic interference in wireless communication channel and random HW failures of transmission system. In the paper there are mentioned the results of simulation of parameters of transmission system and the impact of block length of cryptography code on the resulting of undetected corrupted message are mentioned. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.3506